Avian retrovirus pp32 DNA endonuclease is phosphorylated on Ser in the carboxyl-terminal region. - Horton, R (1988)
The avian retrovirus pp32 DNA endonuclease and the beta polypeptide of the reverse transcriptase contain the same three phosphoserine (p-Ser) tryptic peptides. At least 95% of the Pi label is nearly equally distributed between two major p-Ser tryptic peptides derived from either beta or pp32. These polymerase gene-derived proteins were metabolically labeled with various radioactive amino acids or Pi, and the purified protein was subjected to cyanogen bromide or hydroxylamine cleavage. The results indicated that the two major p-Ser tryptic peptides map to the COOH-termini of both proteins. The two major p-Ser tryptic peptides isolated from Pi-labeled pp32 were subjected to proteolysis by three separate specific proteases. Analysis of the data suggested that these p-Ser are located on pp32 at amino acid positions 262 and 282 from the amino terminus of pp32 (286 amino acids in length). At present, we cannot exclude the possibility that one or both p-Ser peptides map between amino acid positions 124 to 150. The role of this site-specific phosphorylation of pp32 and beta is also discussed.